A Nordic Press: The Development of Printing in Scandinavia and the Baltic States before 1700 from a European Perspective - der Weduwen, Arthur; Cullen, Barnaby (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
Printing emerged more slowly in the Nordic lands than in most parts of Europe. The first active printing press in modern Latvia appeared in 1588; Estonia, Finland and Norway would wait until the 1630s and 1640s respectively. It was also in the seventeenth century that a provincial print trade of any significance would develop in Denmark and Sweden, the two main political powers of the region. While our knowledge of the evolution of printing in the Scandinavian region has long been well established, the print culture of the Nordic lands is often still approached from national perspectives. In this article, we propose to consider the print output of the entire Nordic region – Denmark, the Scandinavian Peninsula, Iceland, Estonia and Latvia – as a single corpus. Using the resources of the Universal Short Title Catalogue project, we will consider what elements unite the history of printing in the region, as well as how distinct Nordic print culture is from that of the rest of Europe. We will consider especially the role of institutions (the church, crown, universities and colleges), foreign agents and linguistic traditions in shaping the print output of the Nordic region before 1700. What emerges from this study is a clear portrayal of the extent to which the Scandinavian book world takes inspiration and diverges from broader European norms. This article will make the case strongly for the importance of studying print culture in a comparative international perspective, and offers broader conclusions on the crucial interactions between print, power and peripheries in early modern Europe.